DERIVATIONAL AFFIXES FOUND ON INSTAGRAM POST OF @POEMSPORN - Andadari, Miftah Karisma Wulan; Maharani, Putu Devi; Winarta, I.B. Gde Nova (Institut Pariwisata dan Bisnis Internasional, 2021)
The study is focused on to find out the types of derivational affixes, the function and the general meaning of each word found in the Instagram Post @poemsporn_. This study is used theory propose by Brinton (2010) and Katamba (1994). The writer used observation procedure method which used before analysing the data. Then, the writer used descriptive-qualitative method. In addition, for presented the data, the writer used an informal method to present the data. This study found there are 34 words that indicated as derivational affixes. The prefixes are 5 words. They consist of prefix (Im-), (a-), (In-), and (Un-). However, there are 29 words that indicated as derivational affixes by adding suffixes (-ing), (-ly), (-ness), (-or), (-ful), (-less), (-ion), (-ance). In addition, for the function of words found are indicated as class changing consist of 33 words, while class maintaining are 2 words. The class changing functions are from verb to noun, adjective to noun, noun to adjective, and adjective to adverb. Meanwhile, the class maintaining function is from adjective to adjective.